Longitudinal association between handgrip strength and depressive symptoms in middle-aged and older Chinese adults: mediating role of functional limitation - Liu, Yanchang; Cui, Junling; Luo, Xin; Wang, Zhuzhu; Shen, Ziyi; Fang, Yan; Li, Chengcheng; Hong, Jingfang (Frontiers in Public Health, 2025)
BackgroundThe relationship between handgrip strength (HGS) at baseline and subsequent depressive symptoms among middle-aged and older Chinese adults remains highly uncertain. This research endeavored to investigate the effect of functional limitation on the association between these two variables.MethodsA total of 5,684 participants aged ≥45 years from the China Longitudinal Study of Health and Retirement (CHARLS) were enrolled, using data from the 2015 and 2018 waves. Functional limitation was evaluated based on participants’ self-reported basic activities of daily living (BADL) and instrumental activities of daily living (IADL). Logistic regression models were utilized to analyze the relationship between HGS and subsequent depressive symptoms, and bootstrap analysis was performed to explore the potential mediating role of functional limitation.ResultsAfter adjusting for confounders, an inverse correlation was detected between HGS and functional limitation (B = -0.885, p < 0.001), a positive correlation was found between functional limitation and subsequent depressive symptoms (B = 1.054, p < 0.001). The mediated effect size of HGS on depressive symptoms through functional limitation was a*b = −0.933 (BCa 95% CI: −1.224, −0.642). Functional limitation had a significant impact on 18.9% of the overall association.ConclusionAmong the Chinese middle-aged and senior population, functional limitation accounted for 18.9% of the connection between HGS and depressive symptoms. Interventions targeting the enhancement of muscle strength should be regarded as crucial elements for maintaining physical function and preventing depressive symptoms.